PEMIKIRAN IBNU KHALDUN TENTANG TARIF PAJAK DAN PENGARUHNYA BAGI BAGI PERTUMBUHAN PEREKONOMIAN (STUDI PADA KITAB MUQADDIMAH) - Khairil Henry; Lusiawati Lusiawati (Faculty of Economic and Social Science, Universitas Islam Negeri Sultan Syarif Kasim, 2025)
Abdul Rahman ibn Mohammad bin Khaldun was one of the most brilliant Muslim scientists and thinker. He was able to explore various fields of study and describe them using scientific language that had never been used by scientists before. The scientific writing style he expressed in concise phrases was actually based on empirical analysis in a historical approach. The concise phrases he wrote in the Muqaddimah are only a basis for Ibn Khaldun's thinking because his discussion would certainly be very broad, such as the discussion of taxation policy and the influence of this policy on economic growth as discussed in this study. This study is based on one of the first volumes of Ibn Khaldun's book Al-I'bar, namely Muqaddimah, which specifically discusses and critiques social phenomena that occurred in the Middle Ages, particularly in the Islamic world. One of the research objects taken from the Muqaddimah is how Ibn Khaldun analyzed taxation, particularly the level/rate of taxation on economic development. This research is qualitative in nature, based on primary and secondary sources that support this research. The discussion is developed to understand Ibn Khaldun's understanding of taxation and how taxation developed in the early, growth, and final stages of the state. The aim is to obtain a complete picture of Ibn Khaldun's thoughts on tax rates and economic growth.